1 - La privatisation des espaces publics dans la ville de Yaoundé (Cameroun) : le cas des activités commerciales - Elom, Paul Ulrich Otye (Africa Development, 2021)
The city of Yaounde is remarkably cosmopolitan, and all of Cameroon’s ethnic groups are represented in its population. This intercultural space allows us to observe that individuals belonging to the same cultural area can often be found together, so that some neighbourhoods resemble villages. This ruralisation, or rather this ‘villagisation’ leads to abusive occupation of space and barely disguised conflicts over land between city natives and newcomers. Thus, one can note that, during ceremonies, roads are often blocked, sometimes for days. Green spaces are subjected to the assaults of would-be farmers. Another phenomenon that causes problems is the sale of public lands by natives who claim to be the owners. Our focus here is on the occupation of public spaces for commercial activities. It is not unusual in the city of Yaounde to find the sidewalks occupied by petty trade and public spaces used by private individuals to build or set up shops or commercial hangars. And when the state at- tempts to resolve the problem as the legitimate owner of public land, it faces resistance from the ‘invaders’ who refuse to leave, so that it is obliged to use force. An anthropological analysis of this phenomenon links the anarchical occupation of public space to the ruralisation of the urban milieu; it is due to the fact that city natives, who no longer have a village and wish to conserve a certain traditionalism, take ownership of these spaces. Grouping individuals together according to their ethnic origins leads them to view their neighbourhoods as their homelands.